IDENTIFIKASI SENYAWA AKTIF ANTIMAKAN BIJI SIRSAK (Annona muricata L.) TERHADAP ULAT KUBIS (Plutella xylostella) - Tabuni, Lusiana; Wahjuni, Sri; Ratnayani, Oka (Jurnal Kimia (Journal of Chemistry); Vol. 8, No. 2 Juli 2014DO - 10.24843/JCHEM.2014.v08.i02.p10, 2014)
Identification of antifeedant active compounds from Soursop seeds (Annona muricata Linn) as natural pesticides against Plutella xylostella has been carried out. 1800 g Soursop seed powder  maceration was applied using methanol and n-hexane resulted in 46.42 g extract of methanol and 94.19 g extract of n-hexane. Viscous extract of methanol was diluted with the mixture of methanol:water (7:3), then evaporated until the entire methanol was removed, and after that it was partitioned with chloroform. The antifeedant activity of viscous extract of n-hexane, chloroform and water was tested which showed that the extract of n-hexane had highest activity compared to the others. Separation of 2 g viscous n-hexane extract with Coloumn Chromatography using Gel Silica 60 and n-hexane:aceton (4:1) as the mobile phase resulted in 5 fractions. The fractions were tested against Plutella xyllostella. The results showed that fraction C had the highest antifeedant activity. The isolate of fraction C was then identified using Gas Chromatography-Mass Spectrometry (GC-MS) based on the data base (Database\NISTO2.L and Database\wiley7n.1) suggested the active compounds were ethyl hexadecanoate ester and 11-octadecanoic acid.
Keywords: Annona Muricata Linn, Antifeedant, Gas Chromatography-Mass Spectrometry, Plutella Xylostella